Evaluation of herbaceous legumes for crop-livestock systems in eastern Indonesia - Kendrick Cox; Jacob Nulik; Neal Dalgliesh; Esnawan Budisantoso; Paskalis Fernandes; Jefrianus Praing; Philip Dida; Jak Uran; Marcel Meomuku; Debora Kana Hau; Tony Basuki; Lindsay Bell (Tropical Grasslands-Forrajes Tropicales)
The sale of cattle presents a significant opportunity to improve livelihoods for smallholder farmers in eastern Indonesia. An opportunity was identified to grow herbaceous forage legumes either in rotation with, or sown within, staple grain crops (maize, rice) to use surplus soil moisture to produce a feed bank for (mostly penned) cattle and potentially increase nitrogen supply to the grain crops. A series of experiments was conducted on Vertisol, Alfisol and Inceptisol soils in lowland and upland districts of eastern Indonesia to identify legumes from 18 taxa suitable for integrated crop-forage systems. Clitoria ternatea and Centrosema pascuorum were found to have best potential for these systems as they established reliably using local methods, consistently ranked highly for herbage yields 2–4 months after sowing and were relatively easy to harvest. Yields were highest on the Vertisol (greatest number of sites) and Inceptisol soils. Lablab purpureus, Macroptilium bracteatum and Mucuna pruriens also ranked high for yield on Vertisol soils. Clitoria ternatea regrew consistently after cutting and forage removal providing potential for extended forage production as growing conditions allow.